2017
DOI: 10.1080/15361055.2017.1293448
|View full text |Cite
|
Sign up to set email alerts
|

Polymer Performance and Aging in a Tritium Environment

Abstract: In an ideal tritium system, we would be able to remove all polymer components due the damage incurred by the resulting beta decay and reduce the required maintenance of the systems and its components. However, polymers are an integral material used within the Tritium Facility in sealing, joining, and containment and are used in several different systems within the process.With the loss of certain capabilities, such as the Normetex pump, it is necessary to identify and/or develop polymers that can better withst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…On the other hand, aluminum, glass, and possibly other materials are well suited to the accommodation step where dissociated atoms are first cooled before entering the trap. Fluorocarbons, however, are not suitable with tritium because they are degraded by radiolysis [273], which leads to the formation of TF, a corrosive gas.…”
Section: B Frequency Techniquesmentioning
confidence: 99%
“…On the other hand, aluminum, glass, and possibly other materials are well suited to the accommodation step where dissociated atoms are first cooled before entering the trap. Fluorocarbons, however, are not suitable with tritium because they are degraded by radiolysis [273], which leads to the formation of TF, a corrosive gas.…”
Section: B Frequency Techniquesmentioning
confidence: 99%
“…We need to derive the expression of the time derivative of the dynamical quantity conjugate to the applied force to calculate the response function from (8). has four terms , , , and , which are calculated by ,…”
Section: Journal Of Advanced Simulation In Science and Engineeringmentioning
confidence: 99%
“…In the decay effect, the chemical bonds break by beta decay of substituted tritium in the molecules to helium-3. Although several experimental and simulation studies have so far been conducted on radiation effects on biomolecules [5,6] and polymeric molecules [7,8], the molecular mechanism of radiation effects on biomolecules and polymeric molecules is not fully understood yet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…14,16) And it is also found that polymeric materials will be damaged in a tritium environment, which leads to lower performance. 18,19) Besides the direct and indirect effects of β-ray irradiation to molecules by tritium, the decay effect, which is caused by hydrogen-tritium exchange and subsequent decays of substituted tritium, also causes damages to the structure of hydrogen-included molecules. It has been studied that tritium can exchange with hydrogen on proteins or small organic molecules.…”
Section: Introductionmentioning
confidence: 99%